Digital storytelling in adult education: barriers and ways to overcome them - Liubov Panchenko (Academy of Cognitive and Natural Sciences, 2021)
In the modern digital globalized world, it is becoming more and more important to train educators in practical application of new tools and technologies, such as digital storytelling. The article substantiates the benefits of digital storytelling and its connection to educational standards; and analyzes the factors that hinder its use. According to the survey of teaching staff and methodologists of different professions during retraining courses, only a quarter of respondents use or have used this method, and about 72% of respondents are ready to consider it. A 3-factor model on possible barriers that impede the using of digital storytelling in education was developed on the basis of the empirical data with the help of a factor analysis tool. The first factor was related to the lack of necessary resources, the second one~-- to resistance to change, the third one -- to the lack of time and lack of technical and methodological support from the educational institution. Possible ways to overcome these barriers are identified. The article describes the structure and content of the special course for educators "Digital Storytelling in Adult Education", aimed at providing methodological support to educators on digital storytelling and its use by discussing the positives, risks, techniques, tools and services, providing experience in creating and sharing digital stories. The content of the stages of involvement of pedagogical staff in the educational practice (orientation, acceptance, evaluation, innovation and institutionalization) is substantiated. The article describes the developed methodological support of the special course: the program of the special course, lectures-presentations on the basics of digital storytelling, examples of practical tasks for implementation and discussion. The article analyzes the ways to use the fragments of massive open online courses on digital storytelling in order to implement blended learning of teaching staff.